Language Attitudes and Motivation in Learning English of Students of Physical Education of FKIP of Universitas Riau - Jismulatif, Jismulatif (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study aimed to find out the attitudes of students of Physical Education towards English based on three components of attitude: cognitive, affective, and conative and to find out the motivation of students of Physical Education in learning English in terms of intrinsic and extrinsic motivation. The research employed descriptive method with quantitative approach. 53 students were taken as the sample of this study selected using total sampling technique, The data were gathered using as set of questioanare which consisted of statement of attitude and motivation aspects. The results of the study showed that the percentage of students attitude toward English in terms of positive cognitive aspect was 88.7% and negative cognitive aspect was 11,3%. This means that the positive cognitive attitude was higher than negative cognitive aspect. In terms of positive affective aspect was 22,6% and negative affective aspect was 77.4% . which were categorized negative affective attitude, it was higher than positive cognitive. While the percentage in terms of negative conative attitude aspects was 96.2% which was categorize as very high and positive conative attitude aspect was 3,8% which was categorize as very low. The result also indecated that the percentage of students extrinsic motivation was 64,2% and intrinsic motivation was 64,2% which were categorized as high